Üriner inkontinanslı kadınlarda cinsel fonksiyonların ve umutsuzluk düzeylerinin incelenmesi - Güney, Demet; Pinar, Sukran Ertekin (Turk Androloji Dernegi, 2024)
OBJECTIVE: The study aims to evaluate sexual functions and levels of hopelessness in women diagnosed with urinary incontinence. MATERIAL and METHODS: The sample for this descriptive research consisted of 111 women admitted to the obstetrics and gynecology department of a training and research hospital in the Black Sea region of Türkiye. The data were collected using the Personal Information Form, Pelvic Organ Prolapse/Urinary Incontinence Sexual Function Questionnaire (PISQ-12), and Beck Hopelessness Scale (BHS). RESULTS: Regarding sexual function, the emotional domain had the lowest score (5.39±4.19), followed by the partner-related domain (9.60±2.17), and the physical domain (17.12±3.28). The mean BHS score was 6.01±4.41. There was a statistically significant negative correlation between the PISQ-12 emotional domain (r=-0.359, p=0.001), physical domain (r=-0.364, p=0.001), PISQ-12 total score (r=-0.499, p=0.001) and the BHS scores. Significant differences were found in women’s PISQ-12 total scores based on age, education, employment status, family type, medication use status, menopause, number of births, and experience of urinary incontinence during sexual intercourse (p<0.05). In addition, statistically significant differences were found in the mean BHS scores based on age, education, menopause status, number of childbirths, and experience of urinary incontinence during sexual intercourse (p<0.05). CONCLUSION: The emotional domain was the most affected domain of sexual function in women. Overall, their sexual functions were less impaired, and levels of hopelessness were generally below average, at a low level. As women’s levels of hopelessness increase, the impact of urinary incontinence on sexual activity in terms of emotional domain and physical domain increases, resulting in an overall deterioration in sexual functions. Keywords: hopelessness, sexual function, urinary incontinence, women
Keywords: 3. Good health